The HIV care cascade: models, measures and moving forward - MacCarthy, Sarah (2015)
Introduction: This article seeks to identify where delays occur along the adult HIV care cascade (‘‘the cascade’’), to improve understanding of what constitutes ‘‘delay’’ at each stage of the cascade and how this can be measured across a range of settings and to inform service delivery efforts. Current metrics are reviewed, measures informed by global guidelines are suggested and areas for further clarification are underscored. Discussion: Questions remain on how best to evaluate late entry into each stage of the cascade. The delayed uptake of HIV testing may be more consistently measured once rapid CD4 testing is administered at the time of HIV testing. For late enrolment, preliminary research has begun to determine how different time intervals for linking to HIV care affect individual health. Regarding treatment, since 2013, the World Health Organization (WHO) and UNAIDS recommend treatment initiation when CD4 B500 cells/mm3; these guidelines provide a useful albeit evolving threshold to define late treatment initiation. Finally,WHO guidelines for high-, low- and middle-income countries also could be used to standardize measures for achieving viral suppression. Conclusions: There is no ‘‘one size fits all’’ model as the provision of services may differ based on a range of factors. Nonetheless, measures informed by global guidelines are needed to more consistently evaluate the scope of and factors associated with delays to each stage of the cascade. Doing so will help identify how practitioners can best deliver services and facilitate access to and continued engagement in care.